Effects of biphenyl on Blaberus craniifer (Blattodea, Blaberidae) cockroaches and their parasites – gregarines and nematodes - O. V. Parhomenko; V. V. Brygadyrenko (Biosystems Diversity, 2023)
In natural ecosystems, parasites and their hosts are subject to xenobiotics, which overall weaken either a host or its parasites. There has been no laboratory study of this process on the example of cockroaches and their parasites. In accurately controlled conditions, we examined the influence of a food supplement – biphenyl – on cockroaches and their three parasites. In the conditions of our experiment, Blaberus cranifer (Blattodea, Blaberidae) cockroaches significantly reduced the rates of anabolism even while consuming the lowest biphenyl concentration in their diet. While the control group was observed to have a 59.4 mg/day increase in body mass, the mass of the cockroaches given biphenyl in the dose of 0.5% of diet mass decreased by 3.4 mg/day on average. Subject to high dosages of biphenyl (0.5–16.0% of fodder mass), body mass of the cockroaches decreased on average by 1.1–9.4 mg/day. The insects consumed their diet at the same rate, no matter the biphenyl concentration given. The number of gregarines Blabericola cubensis (Eugregarinorida, Blabericolidae) and Protomagalhaensia granulosae did not change even at the highest concentration (16.0% of fodder mass) added to the B. craniifer cockroaches’ diet. We observed no significant changes in the amount of larvae of the Cranifera cranifera (Oxyurida, Thelastomatidae) nematodes, while the adult nematodes tended to decline in number when subject to increased concentration of the food supplement in the cockroaches’ food. The number of P. granulosae gregarines did not significantly increase with body-mass gains of their hosts – cockroaches, that is despite increase in volume of their living environment (the midgut of cockroaches) and extension of the period during which the cockroaches consumed gregarine oocysts from the environment with food. Similarly, the number of B. cubensis gregarines also did not significantly change with increased food consumption by the cockroaches. However, we observed a tendency towards greater numbers of this gregarine in the cockroach larvae that were losing mass during the experiment. The greatest mass loss during the experiment was observed in the cockroaches that consumed biphenyl in the diet and had the largest number of C. cranifera nematodes in the hindgut. We observed no significant negative correlation between the numbers of B. cubensis and P. granulosae gregarines. A cockroach that was found to have 70 specimens of B. cubensis in the midgut, had no P. granulosae gregarines. In contrast, when the intestines of a cockroach contained over 10–15 specimens of P. granulosae, some B. cubensis were always present. The number of C. cranifera nematodes in the cockroaches’ hindgut did not depend on the number of B. cubensis or P. granulosae gregarines in their hosts’ midgut. Perhaps, this was related to absence of competition for the intestinal section among them. The regularities we found are different from what we expected to see in the parasitic system prior to the experiment. Gregarines did not compete with nematodes. Neither of them died from biphenyl, though the cockroaches ceased to normally gain weigh when eating biphenyl. That is, the host suffered from biphenyl more than the parasites, even when consuming the lowest concentration of the xenobiotic we tested.